AB0197 Soluble Semaphorin 3E (SEMA3E): A Biomarker for Dysregulation of Vascular Tone Control in Systemic Sclerosis (SSC). (9th June 2015) - Mazzotta, C.; Romano, E.; Bellando-Randone, S.; Manetti, M.; Radicati, A.; Blagojevic, J.; Matucci-Cerinic, M.; Guiducci, S.
Abstract : Background: SSc is a vasculopathy characterised by dysregulation of angiogenesis and vascular tone control leading to severe ischemia and loss of capillaries. In the complex system of interconnection between blood vessels and nerves there is an emerging evidence suggesting that proteins involved in transmitting axonal guidance cues, such as class III semaphorins, play a role in the regulation of vascular development. Sema3E has been shown to repel endothelial cells, modulating the cytoskeleton and focal adhesion structures leading to cellular apoptosis. Objectives: To investigate if soluble Sema3E could be involved in the dysregulation of vascular tone control in primary Raynaud's phenomenon (pRP) and in secondary RP investigating (Very Early Diagnosis of Systemic Sclerosis) VEDOSS and SSc patients. Methods: Sema3E serum levels were measured by quantitative colorimetric sandwich ELISA in 102 pRP serum samples without autoantibodies positivity and without nailfold videocapillaroscopy (NVC) alterations, 100 SSc, 48 VEDOSS patients and 104 age- and sex-matched healthy controls. SSc and VEDOSS patients were evaluated for internal organ damage. Sema3E levels were expressed as median and range and compared by Mann-Whitney U test. p≤0.05 were considered statistically significant. Results: Sema3E levels were significantly increased in pRP (median 1.00 ng/mL, range 0.00-5.84 ng/mL), VEDOSS (median 0.79 ng/mL, range 0.00-1.45 ng/mL) and SSc patients (median 0.85 ng/mL; range 0.00-18.01 ng/mL) versus healthy controls (median 0.55 ng/mL; range 0.00-1.47 ng/mL) (p<0.001). Sema3E was significantly higher in pRP than VEDOSS (p=0.025), while no significant differences were detected between pRP and SSc. In SSc with early NVC pattern, Sema3E levels were significantly increased (median 1.16 ng/mL range 0.63-9.53 ng/mL) in comparison to those detected in the late NVC pattern (median 0.75 ng/mL range 0.00-3.78 ng/mL, p=0.028). Moreover, Sema3E levels were significantly increased in SSc patients without ulcers (median 0.98 ng/mL; range 0.00-18.01 ng/mL) in comparison to those with digital ulcers (median 0.79 ng/mL; range 0.00-3.78 ng/mL, p=0.038). Sema3E was significantly higher in pRP compared to late SSc NVC pattern (p=0.04) and to SSc patients with digital ulcers (p=0.031). Conclusions: Our data show that Sema3E sera levels are significantly increased in pRP, VEDOSS and SSc patients. Circulating Sema3E levels are higher in SSc patients without digital ulcers and with early NVC pattern. In particular, Sema3E may be involved in the early modifications of neuro-vascular mechanisms leading to dysregulation of vascular tone control. Disclosure of Interest: None declared